Purchase and Purchase Binding Agreement as a Production Guarantee Power of Attorney to Impose Mortgage Rights - Andi Rosita; Amin Purnawan; Akhmad Khisni (Sultan Agung Notary Law Review, 2020)
This study aims to: to find out whether the Sale and Purchase Agreement can be used as a guarantee for the making of a power of attorney to impose mortgage rights. The approach method in this research is normative law, the data source is obtained from the literature and the legal materials used are primary, secondary and tertiary legal materials which are then analyzed by means of qualitative analysis.Based on the results of data analysis, it is concluded that the sale and purchase agreement is a manifestation ofthe principle of freedom of contract in which the parties are free to make any kind of agreement they want as contained in Article 1338 of the Civil Code by stating that all agreements made legally are valid as law for those who make them. However,the sale and purchase agreement cannot be used as a guarantee in making the deed of power of attorney to impose mortgage rights because ifthe land rights process has not been completed and the SKMHT period has ended laterthe debtor is in default, the skmht is null and void and the land object which is still in the status of a sale and purchase agreement cannot be subject to security rights and the deed of power of attorney imposing mortgage rights (SKMHT) cannot be upgraded to deed of granting mortgage rights (APHT) which is executorial in nature. The validity period of SKMHT for land that has been registered is one (1) month and creditors have the potential to lose the opportunity to impose mortgage rights.